Eye for an eye [compact disc, unabridged] - Coes, Ben (Coes, Ben. Dewey Andreas novel., 2013)
When assassins kill the person he loves most in the world, Dewey Andreas will risk everything and fight anyone, no matter the cost, for revenge. Dewey Andreas has been instrumental in stopping a series of deadly terrorist attacks, which hasn't gone unnoticed in the darkened corners around the world.